Total Energy of Charged Black Holes in Einstein-Maxwell-Dilaton-Axion Theory - Murat Korunur; Irfan Açıkgöz (Advances in High Energy Physics)
We focus on the energy content (including matter and fields) of the Møller energy-momentum complex in the framework of Einstein-Maxwell-Dilaton-Axion (EMDA) theory using teleparallel gravity. We perform the required calculations for some specific charged black hole models, and we find that total energy distributions associated with asymptotically flat black holes are proportional to the gravitational mass. On the other hand, we see that the energy of the asymptotically nonflat black holes diverge in a limiting case.